TO TEACH THE HISTORY OF THE FORMATION AND FORMATION OF THE FIRST STATES ON THE TERRITORY OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the features of the formation of the first statehood in the territory of Uzbekistan, the Kingdom of Bactria and the formation of the first statehood in the Khorezm oasis. On the basis of research data on the formation of the ancient states of Bactria and Khorezm, the issues of inculcating the history of Uzbek statehood in the minds and hearts of students on the basis of new approaches are described. In history lessons, the topical issues of covering the history of the Uzbek statehood were discussed.